Three magnitude 7 earthquakes on a single fault in central Italy in 1400 years, evidenced by new palaeoseismic results. (29th February 2016) - Galli, Paolo; Giaccio, Biagio; Messina, Paolo; Peronace, Edoardo
Abstract: New palaeoseismic trenching across the main splay of the Fucino fault system provides evidence for a High Middle Age surface‐faulting episode conceivably associated with a disruptive earthquake, similar to the one that occurred in 1915 (Mw 7.0). The existence of this event, which has already been suggested by some previous studies, implies a shortening of the recurrence interval for Mw 7.0 earthquakes with respect to current knowledge. If we assume that the palaeoseismic Holocene record is complete, this shortening is focused in the historical period, when the Fucino structure sourced three strong earthquakes in only 1.4 ka. A similar clustering of energy release in the recent past is consistent with both palaeoseismological studies on other faults affecting the Apennine divide, and the high GPS strain rates observed in the same chain sectors.